2017
DOI: 10.1186/s12929-017-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-butylphthalide protects the heart against ischemic injury and H9c2 cardiomyoblasts against oxidative stress: involvement of mitochondrial function and biogenesis

Abstract: BackgroundMyocardial infarction (MI) is an acute and fatal condition that threatens human health. Dl-3-n-butylphthalide (NBP) has been used for the treatment of acute ischemic stroke. Mitochondria may play a protective role in MI injury. However, there are few reports on the cardioprotective effect of NBP or the potential mitochondrial mechanism for the NBP-induced protection against cardiac ischemia injury. We investigated the therapeutic effects of NBP in an in vivo MI model and an in vitro oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 42 publications
6
30
0
Order By: Relevance
“…Mitochondrial mass, autophagy, and MB also increased in enalapril-treated rats [89]. The increased protein levels of NRF1 and TFAM, which are mitochondrial biogenesis factors, caused the restoration of mtDNA loss by oxidants [83]. Taken together, the increased MB may be a therapeutic strategy for heart injury.…”
Section: Mtdna Homeostasis Associated With Thementioning
confidence: 85%
See 1 more Smart Citation
“…Mitochondrial mass, autophagy, and MB also increased in enalapril-treated rats [89]. The increased protein levels of NRF1 and TFAM, which are mitochondrial biogenesis factors, caused the restoration of mtDNA loss by oxidants [83]. Taken together, the increased MB may be a therapeutic strategy for heart injury.…”
Section: Mtdna Homeostasis Associated With Thementioning
confidence: 85%
“…The increased MB in cardiac aging is considered to be a compensatory maladaptive response to the damaged energy metabolism, which is also stimulated by age-related mtROS. Decreased MB is a vital mechanism responsible for myocardial injury and HF [83,84]. MB alleviates mitochondrial dysfunction induced by oxidative stress and thus is considered to be a novel repair mechanism in aged heart.…”
Section: Mtdna Homeostasis Associated With Thementioning
confidence: 99%
“…The beneficial effect of NBP is attributed to its anti-inflammatory, anti-apoptotic, antioxidant, pro-mitochondrial function, and pro-neurogenesis properties, etc. 9,[11][12][13] Previous studies found that NBP could protect the brain microvascular endothelial cells against oxygen-glucose deprivation (OGD) through increasing HIF-1α and Bcl-2 expression. NBP could also promote angiogenesis through the increased expression of angiogenic growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a well‐known mechanism of MI‐induced injury. Thus, H 2 O 2 is used as oxidative stress model of MI (Tian et al, ). In the present study, in vitro mimic of myocardial ischemic‐induced oxidative stress was carried out by exposing the cultured cardiomyocytes, pretreated with different concentrations of anthocyanidin, to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ROS together with activated JNK and inactive Bcl-2 cause severe damage to the cells, resulting in ischemia injury (Donovan, Becker, Konishi, & Bonni, 2002). Several studies have reported the involvement of ROS-JNK and Bcl-2 signaling in disease pathologies (Tian, He, Yang, & Liu, 2017;Zhu et al, 2018), where inhibition of this pathway had positive effects on disease attenuation (Lee, Lee, Ko, Hong, & Lee, 2010). ROS-induced oxidative injury often involves the participation of JNK and other cell death signaling pathways (Chen et al, 2016;Fan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%